Association between early life factors and accelerometry-based physical activity measures in children aged 5-7 years old - Andrade, Maria Laura Siqueira de Souza; Hardman, Carla Menêses; Barros, Mauro Virgílio Gomes de (Journal of Physical Education (Maringá), 2020)
The present study aims to verify if there is an association between early life factors (birth weight, exclusive breastfeeding, birth order and preterm birth) and accelerometry-based physical activity measures in children aged 5 to 7 years old. It is a cross-sectional study carried out with children from public and private schools in Recife, Brazil. A questionnaire was applied to the children’s parents. Of the 784 children participating in the study, 491 had at least three days of valid monitoring. It was possible to identify that the children classified as the fourth ones, as to birth order, or over, were 83% less likely to have a low percentage of daily time spent on moderate-intensity physical activities compared to firstborns (OR = 0.17; 0.03-0.80). Only birth order was negatively associated with low percentage of daily time spent on moderate physical activities, even after adjustment for confounding factors.